Design,construction and commissioning of microalgae photobioreactor - Ahmad Shafiq, Mohamad (2010)
Oil can potentially be produced by microalgae which then can be converted into biodiesel.Although it has large potential, the design of reactor to grow microalgae nowadays is taking too much space in open ponds and raceways.The objective of this research is to design,construct and commission an airlift photobioreactor which will enable the operator to monitor and control mixing and the level of dissolved CO in the medium and as well exposed it to sunlight for the microalgae to undergo photosynthesis.The construction comprises of two stages namely the first stage on the construction of the 2 vertical airlift photobioreactor which will provide the flow,and the second stage on the construction of the horizontal solar receiver photobioreactor which will enable the microalgae to tap on the sunlight for photosynthesis.The work represented in this thesis concern only on the first stage.For this first stage, the most important factor is the mixing.We can manipulate it by varying the flowrate of air sparged through the airlift bioreactor. There were three series of methods that has been done to complete this research that is design, construct and commissioning process.The design photobioreactor has been used to construct the airlift bioreactor and the support structure.For the commissioning process,blue dye has been used to determine the dispersion pattern in the airlift photobioreactor.It was found that the blue dye was dispersed primarily because of the sparging of the air,even before the flowrate reaches turbulence which would have cause the mixing.After air has been sparged for first try at 2 psi, it takes 2 and a half minute for the dye to complete the cycle in the PBR.For 4 psi,68 seconds,at 6 psi it takes 50 seconds and for the last at 8 psi,it takes 44 seconds for a complete cycle.Even though at 8 psi it takes shorter time to complete a cycle, overflow has been observed at the liquid-gas disengagement chamber.The optimum pressure of air sparged has been determined to be at 6 psi.The research has completely achieved all its objectives.